2018
DOI: 10.1111/evj.12812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and diet on glucose and insulin dynamics in the horse

Abstract: Insulin responses to i.v. and enteral nonstructural carbohydrate challenge increase with age in healthy horses, regardless of diet fed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 45 publications
3
22
0
1
Order By: Relevance
“…Insulin sensitivity appears to decline with age in horses . Given that this also occurs in other species, it is unknown why this outcome was not evident in the current study, but concurrent PPID in some cases could have been a confounding factor.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Insulin sensitivity appears to decline with age in horses . Given that this also occurs in other species, it is unknown why this outcome was not evident in the current study, but concurrent PPID in some cases could have been a confounding factor.…”
Section: Discussionmentioning
confidence: 69%
“…Insulin sensitivity appears to decline with age in horses. 36,37 Given that this also occurs in other species, 38,39 it is unknown why this outcome was not evident in the current study, but concurrent PPID in some cases could have been a confounding factor. However, basal/resting insulin concentration is an insensitive measure of insulin dysregulation in horses, 40 and it is probable that normal resting insulin concentrations were present in some animals with insulin dysregulation in the current study, which would have affected the ability to accurately assess the relationship between insulin sensitivity and age.…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, certain predisposed breeds such as Shetland ponies, donkeys, and miniature horses are frequently not exercised as much as many other breeds as part of standard management. Studies have generally found insulin concentrations to be significantly higher in older versus younger horses and ponies . Circulating adiponectin concentrations are also lower in older animals compared to younger animals, consistent with an age association with ID .…”
Section: Epidemiologymentioning
confidence: 74%
“…However, the improved glucose response seems to indicate that the onset of hyperinsulinemia was not related to tissue resistance to insulin. Diet‐induced improvement in insulin sensitivity has been documented previously in horses and ponies fed starch‐rich, sugar‐rich, or both diets 9,24,25 . A previous study showed that horses and ponies consuming a ration containing a once daily glycemic load for 12 weeks had improved insulin sensitivity based on a frequently sampled intravenous glucose tolerance test (FSIGTT), despite induction of obesity 9 .…”
Section: Discussionmentioning
confidence: 87%